Precise CRISPR-Cas9 Mediated Genome Editing in Super Basmati Rice for Resistance Against Bacterial Blight by Targeting the Major Susceptibility Gene - Zafar, Kashaf; Khan, Muhammad Zuhaib; Amin, Imran; Mukhtar, Zahid; Yasmin, Sumera; Arif, Muhammad; Ejaz, Khansa; Mansoor, Shahid (Frontiers in Plant Science, 2020)
Basmati rice is famous around the world for its flavor, aroma, and long grain. Its demand is increasing worldwide, especially in Asia. However, its production is threatened by various problems faced in the fields, resulting in major crop losses. One of the major problems is bacterial blight caused by Xanthomonas oryzae pv. oryzae (Xoo). Xoo hijacks the host machinery by activating the susceptibility genes (OsSWEET family genes), using its endogenous transcription activator like effectors (TALEs). TALEs have effector binding elements (EBEs) in the promoter region of the OsSWEET genes. Out of six well-known TALEs found to have EBEs in Clade III SWEET genes, four are present in OsSWEET14 gene’s promoter region. Thus, targeting the promoter of OsSWEET14 is very important for creating broad-spectrum resistance. To engineer resistance against bacterial blight, we established CRISPR-Cas9 mediated genome editing in Super Basmati rice by targeting 4 EBEs present in the promoter of OsSWEET14. We were able to obtain four different Super Basmati lines (SB-E1, SB-E2, SB-E3, and SB-E4) having edited EBEs of three TALEs (AvrXa7, PthXo3, and TalF). The edited lines were then evaluated in triplicate for resistance against bacterial blight by choosing one of the locally isolated virulent Xoo strains with AvrXa7 and infecting Super Basmati. The lines with deletions in EBE of AvrXa7 showed resistance against the Xoo strain. Thus, it was confirmed that edited EBEs provide resistance against their respective TALEs present in Xoo strains. In this study up to 9% editing efficiency was obtained. Our findings showed that CRISPR-Cas9 can be harnessed to generate resistance against bacterial blight in indigenous varieties, against locally prevalent Xoo strains.